9(x-6)(5x+4)=0

Divide each term in 9(x-6)(5x+4)=0 by 9.

9(x-6)(5x+4)9=09

Cancel the common factor.

9(x-6)(5x+4)9=09

Divide (x-6)(5x+4) by 1.

(x-6)(5x+4)=09

(x-6)(5x+4)=09

Divide 0 by 9.

(x-6)(5x+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-6=0

5x+4=0

Set the first factor equal to 0.

x-6=0

Add 6 to both sides of the equation.

x=6

x=6

Set the next factor equal to 0.

5x+4=0

Subtract 4 from both sides of the equation.

5x=-4

Divide each term by 5 and simplify.

Divide each term in 5x=-4 by 5.

5×5=-45

Cancel the common factor of 5.

Cancel the common factor.

5×5=-45

Divide x by 1.

x=-45

x=-45

Move the negative in front of the fraction.

x=-45

x=-45

x=-45

The final solution is all the values that make 9(x-6)(5x+4)9=09 true.

x=6,-45

Solve Using the Square Root Property 9(x-6)(5x+4)=0